Financial Inclusion Access: Solution for Sustainable Livelihood Development for Disadvantaged Worrkers: An empirical research survey in Binh Duong province Viet Nam - Nguyen, Hong THU (Advances in Social Sciences Research Journal, 2020)
Financial inclusion access provides services and products to all subjects in a convenient, appropriate and effective manner. This paper aims to test the hypothesis that financial inclusion access contributes to the livelihood development of disadvantaged workers. The paper uses quantitative methods in research with secondary and primary data sources through a practical survey of financial inclusion access in disadvantaged groups. The total observed sample is 325 samples, statistical methods and testing of research hypotheses by analyzing probability prediction from Binary Logistic binary regression model results.The research results have brought more job opportunities for working people, at the same time, the study also found the impact of financial inclusion access on the ability of improving education levels and especially the promulgation of the institutional policies, or increasing financial inclusion access to disadvantaged workers through the empirical research result in Binh Duong province.